2020
DOI: 10.1111/jofi.12964
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Supervision on Bank Performance

Abstract: We explore the impact of supervision on the riskiness, profitability, and growth of U.S. banks. Using data on supervisors' time use, we demonstrate that the top‐ranked banks by size within a supervisory district receive more attention from supervisors, even after controlling for size, complexity, risk, and other characteristics. Using a matched sample approach, we find that these top‐ranked banks that receive more supervisory attention hold less risky loan portfolios, are less volatile, and are less sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(78 citation statements)
references
References 37 publications
(37 reference statements)
5
60
0
Order By: Relevance
“…Empirically, our result is consistent with Pasiouras (2008a) and Luo et al's (2016) findings on global banking industries. Hirtle et al (2016) found similar results in the US bank-holding companies. Official supervisory power is not significantly related to banks' scale efficiency.…”
Section: Impact Of Bank Regulation Supervision and Ownership On Bansupporting
confidence: 68%
“…Empirically, our result is consistent with Pasiouras (2008a) and Luo et al's (2016) findings on global banking industries. Hirtle et al (2016) found similar results in the US bank-holding companies. Official supervisory power is not significantly related to banks' scale efficiency.…”
Section: Impact Of Bank Regulation Supervision and Ownership On Bansupporting
confidence: 68%
“…[], Bushman and Williams []) . Other recent studies have looked at similar questions using quasi‐natural variation in bank regulatory enforcement (e.g., Hirtle, Kovner, and Plosser [], Gopalan, Kalda, and Manela [], Granja []). Nicoletti [] uses variation in regulatory strictness from Agarwal et al.…”
Section: Introductionmentioning
confidence: 99%
“…Hirtle, Kovner, and Plosser (2016) find that modern banks that receive more regulatory scrutiny tend to have more conservative loan loss provisioning practices. Thus, both their results and our results suggest that one channel through which examiners played a role is through the managing of losses.…”
mentioning
confidence: 88%
“…These studies, however, do not provide evidence about whether and how this information is used by supervisors or markets to affect bank behavior. 1 Other studies have found that banks subject to more intensive examinations tend to have lower loan delinquency rates (Rezende and Wu 2014;Hirtle, Kovner, and Plosser 2016), but the mechanism by which this happens remains unclear.…”
Section: Introductionmentioning
confidence: 99%